2008
DOI: 10.1111/j.1365-4632.2008.03538.x
|View full text |Cite
|
Sign up to set email alerts
|

Sporotrichosis in Uttarakhand (India): a report of nine cases

Abstract: Sporotrichosis is also present in north-western region of India as it is reported from north-eastern part. This is the first series of cutaneous sporotrichosis being reported from Uttarakhand, a state situated in the north-western region of India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…De Santis et al [4] reported that first-trimester itraconazole-exposed infants showed no increased risk of congenital abnormalities; however, the rates of spontaneous and induced abortions were higher in the exposed group of pregnant women compared with the control group. Various authors have reported effective treatment of sporotrichosis in pregnant women using thermotherapy [1,3] and even spontaneous resolution during pregnancy [2]. Several infectious diseases, such as malaria, influenza, chickenpox, and measles, may have a markedly severe course [2] and the present cases illustrate the effective treatment of sporotrichosis in pregnancy using thermotherapy or azole therapy after delivery.…”
mentioning
confidence: 77%
“…De Santis et al [4] reported that first-trimester itraconazole-exposed infants showed no increased risk of congenital abnormalities; however, the rates of spontaneous and induced abortions were higher in the exposed group of pregnant women compared with the control group. Various authors have reported effective treatment of sporotrichosis in pregnant women using thermotherapy [1,3] and even spontaneous resolution during pregnancy [2]. Several infectious diseases, such as malaria, influenza, chickenpox, and measles, may have a markedly severe course [2] and the present cases illustrate the effective treatment of sporotrichosis in pregnancy using thermotherapy or azole therapy after delivery.…”
mentioning
confidence: 77%
“…5,6 More recently, in a report of nine sporotrichosis cases published by Agarwal and col. in 2008, one of the patients was pregnant (11.11%) and was treated with local heat, after which the lesions were healed. 7 Local heat therapy is based on fungi thermotolerance and was first described for treatment of chromomycosis by Tagami and col., in 1979. 8 At present, it may be indicated as an effective therapeutic option in subcutaneous mycoses in an otherwise healthy individual, with localized lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant patients, for whom systemic therapy is inadvisable, have been treated with thermotherapy with good results. 13,105,106 In one of these patients, facial sporotrichosis was cleared after about 10 days of microwave diathermy six times daily followed by at-home application of moist heat every 2 awake hours and a nightly heating pad for over 7 months. 105 A pregnant patient with disseminated cutaneous sporotrichosis, a clinical form observed most commonly in immunosuppressed patients and thought to be possible in this patient by the relative immunosuppression of pregnancy, received thermotherapy via 458C water baths for 20 minutes thrice daily for 5 months (2 months during pregnancy and 3 months after delivery), resulting in significant clinical improvement.…”
Section: Subcutaneous Mycosesmentioning
confidence: 99%